Compensatory Vasodilator Mechanisms in the Ophthalmic Artery of Endothelial Nitric Oxide Synthase Gene Knockout Mice - Manicam, Caroline (Sci Rep, 2017)
Nitric oxide (NO) generated by endothelial nitric oxide synthase (eNOS) plays an important role in the maintenance of ocular vascular homeostasis. Therefore, perturbations in vascular NO synthesis have been implicated in the pathogenesis of several ocular diseases. We recently reported that eNOS contributes significantly to vasodilation of the mouse ophthalmic artery. Interestingly, dilatory responses were also retained in eNOS gene-deficient mice (eNOS−/−), indicating inherent endothelial adaptive mechanism(s) that act as back-up systems in chronic absence of eNOS to preserve vasorelaxation. Thus, this study endeavoured to identify the compensatory mechanism(s) in the ophthalmic artery of eNOS−/− mice employing isolated arterial segments and pharmacological inhibitors in vitro. Endothelium removal virtually abolished acetylcholine (ACh)-induced vasodilation, suggesting an obligatory involvement of the endothelium in cholinergic control of vascular tone. However, non-NOS and non-cyclooxygenase components compensate for eNOS deficiency via endothelium-derived hyperpolarizing factors (EDHFs). Notably, arachidonic acid-derived metabolites of the 12-lipoxygenase pathway were key mediators in activating the inwardly rectifying potassium channels to compensate for chronic lack of eNOS. Conclusively, endothelium-dependent cholinergic responses of the ophthalmic artery in the eNOS−/− mice are largely preserved and, this vascular bed has the ability to compensate for the loss of normal vasodilator responses solely via EDHFs.